PHYTOPHARMACOLOGICAL EVALUATION OF ANACARDIUM OCCIDENTALE L. TESTA FROM CASHEW PROCESSING BIOWASTE - Priyanka, P.S. (The Journal of Research ANGRAU, 2026)
The present study was performed during the year 2024 to evaluate and explore the phytopharmacological properties of Anacardium occidentale L. nut testa – a biowaste obtained after cashew kernel processing. The presence of versatile forms of phytochemicals was confirmed by qualitative analysis, whereas anti-nutritional factor analysis revealed no detectable presence.The total phenolic content was quantified, as phenols can contribute to various biological activities. The pharmacological properties of the testawere assessed using in-vitro alpha amylase inhibition assay and in-vitro protein denaturation assay. The former method was used to estimate the anti-diabetic potential and the resultant IC50 value of the standard and extract were 1.77±0.145µg/ml and 2.56 ±0.211µg/ml respectively. The latter method was opted to evaluate the anti-inflammatory potential of the extract. The IC50 values of the standard was 3.17 ±0.221 µg/mland the extract were 4.80 ±0.314 µg/ml. The results of the study showed that the sample contains substantial amounts of phenols, potentially contributing to the significant anti-diabetic and anti-inflammatory activity compared to that of the standards used.Thus, the study aids the research in utilizing cashew nut testa for developing value added products with pharmacological potential.